Fodor's New England 2025 - Bair, Diane; Barry, Jordan (Food writer); Collins, Andrew (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2025)
"Whether you want to visit Cape Cod's beaches, eat lobster in Maine, or ski in Vermont, the local Fodor's travel experts in New England are here to help! Fodor's New England guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos"--